1974
DOI: 10.1042/bj1410627
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in tissue ferritins displayed by gel electrofocusing

Abstract: 1. Horse spleen ferritin and human liver ferritin were examined by gel electrofocusing under conditions that demonstrated equilibrium focusing. Both ferritins were resolved into multiple isoferritins. Both families of isoferritins were separable from one another. 2. Horse spleen ferritin was also resolved into five components by ion-exchange chromatography on DEAE-Sephadex A-50. Each of the major chromatographic fractions contained only a few of the isoferritins seen on gel electrofocusing. Each chromatographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
27
2
2

Year Published

1975
1975
1998
1998

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 41 publications
3
27
2
2
Order By: Relevance
“…W e have shown that thc isoferritin profiles obtained in our system do, in fact, represent equilibrium banding patterns (Drysdale, 1974). Furthermore, similar patterns are also obtained by isoelectric focusing in sucrosc density gradients or in Scphadex bcds (Alpert et al, 1973 ;Righetti 8~ Drysdale, 1974;.…”
Section: Dr Drysdale and Rolkagircs Reply Asfo/lowssupporting
confidence: 75%
See 1 more Smart Citation
“…W e have shown that thc isoferritin profiles obtained in our system do, in fact, represent equilibrium banding patterns (Drysdale, 1974). Furthermore, similar patterns are also obtained by isoelectric focusing in sucrosc density gradients or in Scphadex bcds (Alpert et al, 1973 ;Righetti 8~ Drysdale, 1974;.…”
Section: Dr Drysdale and Rolkagircs Reply Asfo/lowssupporting
confidence: 75%
“…All of Dr Richter's arguments suggesting that the multiple forms arc coiitamiiiaiits or artifacts resulting froin aggregates or ampholytc binding have already been fully answered in the past few years (Drysdale, 1970(Drysdale, , 1974Urushizaki et al, 1971Urushizaki et al, , 1973.…”
Section: Dr Drysdale and Rolkagircs Reply Asfo/lowsmentioning
confidence: 99%
“…Ferritin is separated in isoferritins by iso electric focusing [10]. In different organs different isoferritins were found [18,22,28], These results were confirmed by ani on-exchange chromatography [10,29,31].…”
Section: Discussionsupporting
confidence: 65%
“…Elevated levels have been reported in leukaemia and Hodgkin's disease (Jones et al, 1973) and, in the case of acute leukaemia, this is associated with increased synthesis and high concentrations in the malignant cells White et al, 1974). The analysis of normal tissue ferritin by isoelectric focusing has revealed considerable heterogeneity (Drysdale, 1974;Powell et al, 1975). Alpert, Coston and Drysdale (1973) found human hepatoma tissue to contain an acidic ferritin also present in early foetal liver but not in mature liver.…”
mentioning
confidence: 99%